Effect of Resin Infiltration and Microabrasion on the Microhardness of the Artificial White Spot Lesions (An in Vitro Study) - Al-Mamoori, Reem Majeed H.J.; Al Haidar, Aseel Haidar M.J. (Journal of Baghdad College of Dentistry, 2022)
Background: White spot lesion is the first visible sign of dental caries that is characterized by demineralized lesion underneath an intact surface. Several studies demonstrated that they could be treated using noninvasive techniques like the use of fluoride or casein phospho-peptide and amorphous calcium phosphate. Improvement in aesthetic outcomes by covering the demineralized enamel is one of the advantages of the use of resin infiltration and opal-ustre microabrasion, which are two new techniques that had been used for treatment of white spot lesion. The purpose of this study was to evaluate the impact of resin infiltration and microabrasion in the microhardness of the artificial white spot lesions at various depths. Material and method: Forty-eight artificially white spot lesions were divided into three groups (n=16) according to the depth of the lesion (shallow enamel, deep enamel, shallow dentine). Then, each of the main groups was divided into two subgroups (n = 8), the first group was treated with resin infiltration, while the second one was treated with Opalustre microabrasion. Assessment of the microhardness was done using Vickers hardness at the baseline, after demineralization (formation of the white spot lesion) and after the treatment with the resin infiltration and the microabrasion. Results: There was a significant difference in the microhardness of all the layers after demineralization. Although the hardness values that found among the icon group in the inner enamel and the outer dentine were higher than that of the opalustre, statistically there was no significant difference between the two mate-rials in all the layers of the white spot lesion. Conclusion: Microhardness values decrease as the depth of the white spot lesion increase. There was an increase in the microhardness values after the treatment with the resin infiltration and the microabrasion.